Age differences and brain maturation provide insight into heterogeneous results in autism spectrum disorder - O’Hearn, Kirsten; Lynn, Andrew (Frontiers in Human Neuroscience, 2023)
Studies comparing individuals with autism spectrum disorder (ASD) to typically developing (TD) peers have yielded inconsistent results. These inconsistencies reflect, in part, different patterns of development in those with ASD compared to TD peers leading to heterogeneity in both groups. These disparate trajectories were evident in our studies and studies from other laboratories using the same recruiting source. After summarizing these results, we review evidence on age-related changes in other samples. Often, there are age-related behavioral improvements from adolescence to adulthood in the TD group, which are associated with maturation of the striatal and temporal lobes into adulthood typically, that are not evident in groups with ASD. While this pattern was evident across both social and non-social tasks, the difference between TD and ASD trajectories was most robust on a social task, face recognition. While tempting to ascribe this to social deficits in ASD, it may actually reflect the strikingly prolonged typical development of social cognition (e.g., face recognition). This review suggests that individuals with ASD exhibit a lack of late developmental improvement on skills important for navigating the transition to adulthood, including execution function and decision making, social cognition and communication, and emotional recognition and self-awareness. This is consistent with neuroimaging studies indicating arrested or atypical brain maturation in temporal and frontal regions during adolescence in ASD. These results highlight the importance of a developmental framework and explicit consideration of age and/or developmental stage when studying ASD.